The logic of defence assistance to Ukraine - Dumitru Minzarari; Susan Stewart (Stiftung Wissenschaft und Politik (SWP), 2021)
The recent debate about providing military assistance to Ukraine has relevance for the efforts to overcome the current impasse in the Minsk Process and the Normandy Format in particular, and thus the search for a resolution to the conflict regarding the Donbas. But it also concerns larger questions of Germany's role in Europe, and in security policy more generally. It touches on Germany's ability to adapt to situations in which other countries are willing to envisage military solutions to existing conflicts. In this sense, it fits into discussions about a more geopolitical EU. And it offers Berlin a way to reinforce its commitment to European security and stability by more actively resisting the redrawing of international borders.
Keywords: 320